Down scaled Kjeldahl digestion and flow injection conductometric system for determination of protein content in some traditional northern Thai foods - Pattama Yanu (2018)
© 2017 Elsevier Ltd A flow injection conductometric (FIC) system for determination of total Kjeldahl nitrogen (TKN) was developed for estimating total protein content in food. A small scale Kjeldahl digestion was performed with a short digestion time of only 20 min. The digested solution was injected into the FIC system, and TKN was converted to ammonia gas in an alkaline donor stream of the system. The gas diffused through a membrane and dissolved into an acceptor stream causing an increase in conductivity as detected by a detector and recorded as a peak. Under the optimum condition, a linear calibration graph in the range of 4.00–100.00 mg L−1was obtained with LOD of 0.05 mg L−1. A good precision (0.04% RSD, n = 11, 30.00 mg N L−1) and high sample throughput of 72 h−1was achieved. The method was applied for determination of protein in some traditional northern Thai foods, revealing that they are good sources of proteins.